Correlation between Membrane Permeability and the Intracellular Degradation Activity of Proteolysis-Targeting Chimeras - Yokoo, Hidetomo; Osawa, Hinata; Saito, Kosuke; Demizu, Yosuke (Chemical & pharmaceutical bulletin, 2024)
Proteolysis-targeting chimeras (PROTACs) have attracted attention as an innovative drug modality that induces the selective degradation of target proteins. This technology shows higher activity than conventional inhibitors and holds great potential in the field of drug discovery. Optimization of the linker is essential for PROTACs to achieve sufficient activity, particularly with regard to cell membrane permeability. However, the correlation between membrane permeability and the activity of PROTACs has not been fully explored. To address this, we established a new molecular design approach to remove the linker and optimize PROTAC structure. These PROTAC compound groups were used to analyze the correlation between membrane permeability and activity using LC-tandem mass spectrometry (LC-MS/MS). Results revealed that the degradation activity of PROTACs fluctuates with increasing membrane permeability and changes in response to linker optimization, while sufficient proteolytic activity can be retained. These findings demonstrate the importance of considering the balance between membrane permeability and activity in PROTAC design and provide a new strategy for developing more effective PROTACs.